A model for brittle failure in adhesive lap joints of arbitrary joint configuration. (1st December 2015) - Stein, N.; Weißgraeber, P.; Becker, W.
Abstract: In this work an efficient general Finite Fracture Mechanics model for crack initiation in adhesively bonded joints is presented which is applicable to various joint configurations with shear flexible laminate and metallic adherends. The mechanical behaviour of the adhesive joints is modeled by a general sandwich-type model for the analysis of bonded joints with composite adherends which gives solutions for the peel and shear stresses in the adhesive. The failure behaviour is described by a physically sound combined stress and energy criterion which requires only two basic failure parameters: the strength and the fracture toughness of the adhesive. The implicit equations are solved with a highly efficient iterative solution scheme. In a comprehensive study, experimental and numerical results of an elaborated Cohesive Zone Model (CZM) are used for comparison. It is shown that the predicted failure loads are in good to very good agreement with the experimentally determined results and the effects of the geometric parameters on the failure load are rendered correctly.